2004
DOI: 10.1021/np030374g
|View full text |Cite
|
Sign up to set email alerts
|

A New 3,4-seco-Lupane Derivative from Lasianthus gardneri

Abstract: A new seco-ring A lupane triterpene derivative (1), along with lupenone, lupeol, beta-sitosterol, ursolic acid, and stigmasterol 3-O-beta-d-glucoside, were isolated from a methanol extract of mature stems of Lasianthus gardneri, a shrub from the family Rubiaceae growing in Sri Lanka. The structure and stereochemistry of the new compound were determined using a combination of (13)C and (1)H homo- and heteronuclear 2D NMR experiments and from mass spectral data. The structure of 1 was confirmed by partial synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…Finally, at the characteristic chemical shift for an α ‐methylene group joined to a carboxyl group of δ H 2.16 (ddd, J = 2.8, 5.2, 8.8 Hz), resonance signals from two hydrogens were observed ( vide supra ). All spectroscopic characteristics define this natural product as a 3,4‐ seco ‐lupane‐type triterpene that contains a carboxyl group on C‐2 and an isopropyl group on C‐5, establishing the structure as 3,4‐ seco ‐lup‐20(29)‐ en ‐3‐oic acid ( 1 ). Accordingly, 30 signals were observable in 13 C NMR spectrum.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Finally, at the characteristic chemical shift for an α ‐methylene group joined to a carboxyl group of δ H 2.16 (ddd, J = 2.8, 5.2, 8.8 Hz), resonance signals from two hydrogens were observed ( vide supra ). All spectroscopic characteristics define this natural product as a 3,4‐ seco ‐lupane‐type triterpene that contains a carboxyl group on C‐2 and an isopropyl group on C‐5, establishing the structure as 3,4‐ seco ‐lup‐20(29)‐ en ‐3‐oic acid ( 1 ). Accordingly, 30 signals were observable in 13 C NMR spectrum.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Betulinic acid has attracted attention due to its anticancer 131 and chemotherapeutic potential. 132 The seco-lupanes 200 and 201 have been isolated from Adelanthus lindenbergianus 133 and Lasianthus garneri, 134 respectively. The structure of lupeportlandol 202, from Euphorbia portlandica, was confirmed by X-ray analysis as the This journal is © The Royal Society of Chemistry 2007 3,19-diepimer of lupeol.…”
Section: The Lupane Groupmentioning
confidence: 99%
“…Later, this classification was approved by investigation of 35 selected Rubiaceae plants by TLC, GC, and GC-MS; the result revealed that asperuloside and deacetylasperulosidic acid occur in most plants of the Rubioideae subfamily, especially in Lasianthus species [ 4 ]. Previous phytochemical studies on some Lasianthus species revealed the presence of iridoids, iridoid glycosides, anthraquinones, and terpenes [ 5 , 6 , 7 , 8 , 9 , 10 ]. In our previous study, we isolated a bis-iridoid glycoside from L. wallichii for the first time [ 11 ] and five undescribed iridane type glycosides, lasianosides A–E, from L. verticillatus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%